Corroborating of Depression, Anxiety, and Stress Scale-21 items (DASS-21) and the Perceived Stress Scale-10 items (PSS-10) and Psychological Features in patients with periodontitis: a questionnaire study - Kalluri, Yasasvi; Chakravarthy, Y.S.H.S; Reddy, D Bharath Simha; Nimmala, Sri Ram Naidu; Pabbineedi, Sai Satya Sri; Gathram, Prathyusha (International Journal of Dental Materials, 2024)
Background: Periodontitis is a multi-factorial inflammatory disease that, if left untreated, can lead to tooth loss. Stress is considered one of the key contributors that can worsen the condition. Research has shown that psychological factors may activate immune responses in the host, promoting changes that facilitate the progression of periodontitis. Therefore, clinicians need to utilize psychological self-assessment scales to measure anxiety, depression, and stress in patients suffering from periodontitis. Aim: To investigate the psychometric properties of the Depression, Anxiety, and Stress Scale - 21 Items (DASS-21) and 10-item Perceived Stress Scale (PSS-10) in patients with periodontitis and to evaluate the psychological features of patients with periodontitis. Materials and methods: This descriptive cross-sectional study involved 300 patients diagnosed with periodontitis, conducted over three months. The participants were given the DASS-21 and PSS-10 questionnaires and completed them independently, responding based on their initial reactions. The DASS-21 comprises 21 items designed to assess levels of depression, anxiety, and stress, whereas the PSS-10 contains 10 items intended to gauge perceived stress levels. Results: The mean and SD scores of patients using PSS-10 and DASS-21 were 16.79 ± 4.90 and 14.12 ± 5.04, respectively. The T-value was 6.56 with a p-value of 0.000. According to the findings of this study, there was a statistically significant (p=0.000) association between the PSS 10 Scale and the DASS 21 scale. Conclusion: The DASS-21 and the PSS-10 can be used as general measures for psychological assessment in patients with periodontitis.